Android Application for Car Black Box with Cloud Storage - Wan Ismail, Wan Hazimah; Mohd Husny, Herny Ramadhani; Ya Abdullah, Norhaiza; Anak Janang, Clarence Indit (Journal of Computing Technologies and Creative Content, 2017)
In Malaysia, a lot of concern is directed towards road accident statistics which rises alarmingly high especially during the festive breaks. Evidence from the accident cases are very important for investigation purpose in order to know the root cause of the incident. Normally, the evidence can be obtained from the black box recorder of the vehicles.  Car black box is a car travelling data recorder where it used in a car as digital electronic recording equipment. The data from the car black box is vital as it can be used for both the police and insurance companies in reconstruction of the events before the accident or related crimes. Besides that, it will also bring a number of benefits for the car’s owner. Therefore, the rising of new technology nowadays has brought a lot of revolution in new invention of car black box. It brings to new invention of traditional car black box into new type of mobile application car black box which is design for android smartphone. Smartphone has been chosen as a medium for this application since everyone is using smartphone as a part of their life need as its mobility and convenience to users. Besides that, the requirement based on android application able to help them solve their problems in daily life is high. Car Black Box Mobile Application with Cloud System was developed to allow the car user to record video and Google Maps route as their evidence if user was involved in a car accident or related crimes. This application able to protect the data from loses and ruined by the unauthorized user where it has cloud data backup system and it also implemented AES-128 encryption method in order to secure the data. It is very significant to have this application as it can help the car’s owner, police and insurance companies for investigating car accidents or crimes according to the evidence.